Morphology, Conductivity, and Mechanical Properties of Electropolymerized Polypyrrole/Silver-Coated Granular Microsphere Composite Films - Advincula, Al Otayde (Archīum Ateneo, 2021)
We report a facile synthesis of polypyrrole/silver-coated granular microsphere composite films through electropolymerization process in the presence of low- and high-density conductive granular microspheres. The resulting morphologies of composite films were implicitly influenced by the density of microspheres as revealed by scanning electron microscopy (SEM). Energy-dispersive X-ray (EDX) analysis confirmed the existence of elemental composition of the polypyrrole and conductive microspheres, while Fourier transform infrared (FTIR) spectroscopy verified the presence of molecular bonding associated with the dopant anion in all the synthesized films. Resistivity measurements demonstrated enhanced nonlinear conductivity and a strong dependence of current density in composite films with increasing application of electric field. Improvement in nonlinear conductivities is linked to the formation of more effective conductive pathways that boosted intermolecular and inter-particle charge carrier migration. Tensile tests reveal that the conductive granular microspheres have the general tendency to decrease internal forces in composite films.